Learning and Its Neural Correlates in a Virtual Environment for Honeybees - Zwaka, Hanna; Bartels, Ruth; Lehfeldt, Sophie; Jusyte, Meida; Hantke, Sören; Menzel, Simon; Gora, Jacob; Alberdi, Rafael; Menzel, Randolf (Frontiers in Behavioral Neuroscience, 2019)
The search for neural correlates of operant and observational learning requires a combination of two (experimental) conditions that are very difficult to combine: stable recording from high order neurons and free movement of the animal in a rather natural environment. We developed a virtual environment (VE) that simulates a simplified 3D world for honeybees walking stationary on an air-supported spherical treadmill. We show that honeybees perceive the stimuli in the VE as meaningful by transferring learned information from free flight to the virtual world. In search for neural correlates of learning in the VE, mushroom body extrinsic neurons were recorded over days during learning. We found changes in the neural activity specific to the rewarded and unrewarded visual stimuli. Our results suggest an involvement of the mushroom body extrinsic neurons in operant learning in the honeybee (Apis mellifera).